A graph theory study of resting-state functional connectivity in children with Tourette syndrome. (May 2020) - Openneer, Thaïra J.C.; Marsman, Jan-Bernard C.; van der Meer, Dennis; Forde, Natalie J.; Akkermans, Sophie E.A.; Naaijen, Jilly; Buitelaar, Jan K.; Dietrich, Andrea; Hoekstra, Pieter J.
Abstract: Little is known about the brain's functional organization during resting-state in children with Tourette syndrome (TS). We aimed to investigate this with a specific focus on the role of comorbid attention-deficit/hyperactivity disorder (ADHD). We applied graph theoretical analysis to resting-state functional magnetic resonance imaging data of 109 8-to-12-year-old children with TS ( n = 46), ADHD without tics ( n = 23), and healthy controls ( n = 40). First, we compared these three groups, and in a second comparison four groups, distinguishing TS with (TS + ADHD, n = 19) and without comorbid ADHD (TS−ADHD, n = 27). Weighted brain graphs were constructed for both comparisons to investigate global efficiency, local efficiency, and clustering coefficient per acquired network. Local efficiency and clustering coefficient were significantly lower in children with TS−ADHD in the default mode network compared with healthy controls, and in the frontoparietal network compared with ADHD; we also found associations with higher tic severity. Our study supports a different functional brain network organization in children with TS−ADHD, compared with healthy controls and children with ADHD.